EFFECTIVENESS OF THE ARKA METHOD IN IMPROVING SPEAKING ABILITY - Cici S; Nasya Dinda Afrilla; Charmelia Nuraini (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to ascertain how well SMP Kota Cirebon's speaking abilities may be enhanced by the ARKA approach. Quantitative research using a survey design is the methodology employed. Surveys and closed tests measuring the six aspects of speaking ability—pronunciation, grammar, vocabulary, fluency, understanding, and tasks—were used to gather data. SPSS version 25 was used for data analysis. The findings show that SMP Kota Cirebon's speaking ability had been significantly affected by the ARKA approach. This is demonstrated by the coefficient of determination (R Square) value of 0.636, which indicates that the ARKA approach accounts for 63.6% of the diversity in students' speaking ability. In addition, the multiple linear regression model is statistically significant (Sig. = 0.000 < 0.05), according to the ANOVA test findings. According to the study's findings, junior high school students' speaking abilities can be enhanced by the ARKA technique, which is also a creative and relaxing alternative teaching strategy.